Respuesta :

2y-2>-4+2. Add 2 to both sides. Now you have 2y>-2+2. Erm. I might be wrong since I JUST learned this unit and I made some mistakes. Ok soo, add 2 to both sides again. Now you have 2y+2>2. Subtract 2 from both sides. You now have 2y>0. You have no solution since 2 can't be divided by 0. I'm probably wrong but I hope I helped...ish.
2(y-2)>-4+2y. so distribute out the two first==>
2y-4>-4+2y. then add four to both sides==>
2y>2y. then subtract by 2y on both sides==>
you get 0. so basically this function doesn't work or it's not a function